The Use of Constellation Design Technique in Teaching Writing to the Tenth Grade Students of SMA Negeri 5 Lubuklinggau - Wulandari, Aprica; Ardayati, Ardayati; Episiasi, Episiasi (Journal of English Education, Literature and Linguistics, 2024)
The problem of this study was “was it significantly effective to teach writing by using Constellation DesignTechnique to the tenth grade students of SMA Negeri 5 Lubuklinggau”? The objective of this study was to find out whether or not it was significantly effective to teach writing by using Constellation Design Technique to the tenth grade students of SMA Negeri 5 Lubuklinggau. The method was a pre-experimental with one group pre-test post-test design. The population of this study was all the tenth grade students of SMA Negeri 5 Lubuklinggau that consisting of 148 students. The sample was taken through cluster random sampling. The number of the sample was 38 students. The writing test was used in collecting the data. The data analyzed through three techniques: 1) Individual Score, 2) Comparison to Minimum Mastery Criteria, and 3) Matched t-test. The results of this study: (1) The mean score of pre-test was 64.61, (2) The mean score of post-test was 73.39, and (3) the result of matched t-test was 5.73, which was higher than 1.697 as the critical value of the ttable of degree of freedom 37 with 95% significant level for one tailed-test. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that it was effective to teach writing by using Constellation Design Technique to the tenth grade students of SMA Negeri 5 Lubuklinggau.